Peramalan Indeks Harga Konsumen (IHK) Kota Tarakan dengan Metode Double Exponential Smoothing dari Brown - St Syahdan; Siti Aisyah (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2020)
The Tarakan City Consumer Price Index (CPI) shows trend patterns. This research is applied research with the aim of determining the best parameters and forecast results of Tarakan City CPI from January to May 2019 with the Double Exponential Smoothing method from Brown. The results of the Tarakan City CPI forecasting with the best parameters  0,5 with MAPE value = 0,670 from January to May 2019, respectively are 147,652; 148,481; 149,309; 150,138  and  150,966. These results indicate that the forecast of CPI in Tarakan City has increased every month. The higher the CPI value, the faster the inflation rate will have an impact on the rising prices of goods and services. By knowing CPI forecasting that continues to increase, the purchase of inventory of goods and services can be accelerated in order to avoid purchasing higher inventory.